2013
DOI: 10.3389/fnhum.2013.00506
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment may protect against hippocampal atrophy in the chronic stages of traumatic brain injury

Abstract: Objective: To examine the relationship between environmental enrichment (EE) and hippocampal atrophy in the chronic stages of moderate to severe traumatic brain injury (TBI).Design: Retrospective analysis of prospectively collected data; observational, within-subjects.Participants: Patients (N = 25) with moderate to severe TBI.Measures: Primary predictors: (1) An aggregate of self-report rating of EE (comprising hours of cognitive, physical, and social activities) at 5 months post-injury; (2) pre-injury years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 69 publications
(89 reference statements)
0
42
0
Order By: Relevance
“…Additionally, Miller et al (2013) have also recently demonstrated a decrease in hippocampal volume loss in TBI patients, with increased engagement with cognitively, physically and socially demanding activities, supporting the role of EE in directly preventing neuronal death.…”
Section: Mechanisms Promoting Improved Behavioral and Pathological Rementioning
confidence: 85%
“…Additionally, Miller et al (2013) have also recently demonstrated a decrease in hippocampal volume loss in TBI patients, with increased engagement with cognitively, physically and socially demanding activities, supporting the role of EE in directly preventing neuronal death.…”
Section: Mechanisms Promoting Improved Behavioral and Pathological Rementioning
confidence: 85%
“…Families were the site of social enrichment, facilitating engagement with services and transport to and from important health care and rehabilitation activities (Miller, Colella, & Green, 2013). Postinjury adjustment is driven by social identity processes that can cut both ways.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent clinical research has demonstrated the efficacy of EE in promoting neurorehabilitation, such as in stroke and traumatic brain injury (TBI) patients . Of note, neuropathic pain is prevalent after stroke and TBI .…”
Section: Translational Perspectives Of Ee For Neuropathic Painmentioning
confidence: 99%
“…More importantly, a clinical magnetic resonance imaging (MRI) study revealed that EE could prevent bilateral hippocampal atrophy in patients for up to 28 months post‐TBI, with cognitive activity variations playing the dominant role in eliciting the neuroanatomical changes . Meanwhile, hippocampal shrinkage was recognized as an intriguing feature that appeared specific to neuropathic pain.…”
Section: Translational Perspectives Of Ee For Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation